2022
DOI: 10.3390/ma15113985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rolling Treatment on Microstructure, Mechanical Properties, and Corrosion Properties of WE43 Alloy

Abstract: Magnesium alloys show broad application prospects as biodegradable implanting materials due to their good biocompatibility, mechanical compatibility, and degradability. However, the influence mechanism of microstructure evolution during forming on the mechanical properties and corrosion resistance of the magnesium alloy process is not clear. Here, the effects of rolling deformation, such as cold rolling, warm rolling, and hot rolling, on the microstructure, mechanical properties, and corrosion resistance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As a result, electrochemical processes were weakened and corrosion rates were reduced in highly deformed samples [ 18 ]. In the work of Deng et al, the WE43 alloy also showed better corrosion resistance in the hot rolled specimens [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, electrochemical processes were weakened and corrosion rates were reduced in highly deformed samples [ 18 ]. In the work of Deng et al, the WE43 alloy also showed better corrosion resistance in the hot rolled specimens [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Often a positive effect is reported, when smaller grain size leads to a finer distribution of precipitates at grain boundaries, e.g. [ 17 ]. Obviously, this is not an issue for the high-purity platinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cold rolling of magnesium alloys leads to a high density of dislocations and deformation twins, significantly contributing to strain hardening. This process can adversely affect the anisotropic behavior due to the development of a strong basal texture [10,11]. However, the strain hardening from cold rolling also increases the yield strength and tensile strength of the Mg alloys.…”
Section: Introductionmentioning
confidence: 99%